Functionally Gradient Concrete // Resource- and emission-reduced concrete building construction system for NZ - The development of a seismically resistant joint for a functionally graded concrete wall-to-floor connection. Issue 1 (1st September 2022) - Oswald, F; Haase, W; Blandini, L; Sobek, W; Henry, R; Nikolic, D
Abstract: Concrete is known to have a large carbon footprint; however, its versatility and durability are unparalleled. These qualities pertain to the usefulness of concrete in an ever-increasing population, and therefore demand our attention. By optimizing and improving the performance of concrete through innovative technologies, such as functionally graded concrete, the carbon footprint can be reduced. In construction, the weight of a conventional concrete structure accounts for approximately 70 % of a building's total mass. In comparison, functionally graded concrete (FGC) is 50-60 % lighter, accounts for reduced emissions (45-60 %), and has improved insulative properties. These factors are achieved by its increased porosity and efficiency of material. Additionally, in comparison to a conventional concrete system, less raw material would be needed to achieve the same structural requirements and therefore less resources would be required. By varying its density, FGC creates a purely mineral, multifunctional, mono-material element that is fully recyclable. Investigations into implementing FGC as a building component in seismic areas have not yet been carried out. The development of a seismically resistant joint for a FGC wall-to-floor connection is necessary due to seismic requirements present around the world. The project presents a review of existing seismic resilient connection technologies, their classification to small scale and largescale building typologies, and the development of concepts for FGC seismically resilient wall-to-floor connections.